2006
DOI: 10.1038/sj.eye.6702222
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up after intravitreal triamcinolone acetonide for exudative age-related macular degeneration

Abstract: Purpose To report on the follow-up of patients who received an intravitreal triamcinolone acetonide injection (IVTA) as treatment of exudative age-related macular degeneration.Methods The clinical interventional caseseries study included 205 patients (222 eyes) with progressive exudative age-related macular degeneration with subfoveal neovascularization who consecutively received an IVTA of about 20 mg as only therapeutic procedure and for whom follow-up was at least 3 months. Mean follow-up was 10.477.1 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
1
13
0
3
Order By: Relevance
“…Although there were differences between the studies in the type of subfoveal neovascularization, the dosage of TA, and the timing of the follow-up examinations, the randomized controlled study by Gillies et al [123] may be a landmark study cautioning against the use of TA as a monotherapy for exudative AMD. In agreement with Gillies et al [123], a recent follow-up study on 205 patients who received IVTA as a monotherapy for the treatment of exudative AMD reported that visual acuity at 6, 9 and 12 months after the injection was significantly (p < 0.001) lower than visual acuity at the baseline of the study [136]. The mean loss at 6 months was 1.4 ± 3.8 Snellen lines, at 9 months it was 2.5 ± 4.6 lines, and at 12 months after the injection it was 2.6 ± 4.0 lines.…”
Section: Clinical Studies: Ta In Other Ocular Diseasessupporting
confidence: 86%
See 1 more Smart Citation
“…Although there were differences between the studies in the type of subfoveal neovascularization, the dosage of TA, and the timing of the follow-up examinations, the randomized controlled study by Gillies et al [123] may be a landmark study cautioning against the use of TA as a monotherapy for exudative AMD. In agreement with Gillies et al [123], a recent follow-up study on 205 patients who received IVTA as a monotherapy for the treatment of exudative AMD reported that visual acuity at 6, 9 and 12 months after the injection was significantly (p < 0.001) lower than visual acuity at the baseline of the study [136]. The mean loss at 6 months was 1.4 ± 3.8 Snellen lines, at 9 months it was 2.5 ± 4.6 lines, and at 12 months after the injection it was 2.6 ± 4.0 lines.…”
Section: Clinical Studies: Ta In Other Ocular Diseasessupporting
confidence: 86%
“…IVTA has been discussed to be a possibly useful adjunct to the therapy of exudative AMD [116,117,118,119,120,121,122,123,124,125,126,127,128,129,130,131,132,133,134,135,136,137,138,139,140,141,142,143,144,145,146,147,148,149,150,151,152] since previous studies had shown that TA may have an antiangiogenic and antiedematous effect [112,113,114,115,258,259,260,262,263,264,265,266]. Both neovascularization and retinal edema are characteristics of exudative AMD.…”
Section: Clinical Studies: Ta In Other Ocular Diseasesmentioning
confidence: 99%
“…In agreement with Gillies et al, a recent follow-up study on 205 patients who received intravitreal triamcinolone as monotherapy for the treatment of exudative age-related macular degeneration reported that visual acuity at 6 months, 9 months and at 12 months after the injection was significantly (p ! 0.001) lower than visual acuity at baseline of the study [137] . Mean loss at 6 months was 1.4 8 3.8 Snellen lines, at 9 months, 2.5 8 4.6 lines, and at 12 months after the injection, 2.6 8 4.0 lines.…”
Section: Exudative Age-related Macular Degeneration Treated By Intravmentioning
confidence: 74%
“…Intravitreal triamcinolone as a monotherapy of a single injection of a high dosage (20 mg) did not show an apparent benefit at 12 months after injection in patients with neovascular AMD [57], whereas combined IVTA and PDT showed even better results than PDT as a single procedure. Chan et al [58] compared 24 eyes that were treated with combined PDT with IVTA to a control group of 24 eyes which received PDT as a monotherapy and found the combined treatment regimen statistically more effective at 12 months for stabilization of vision.…”
Section: Current and Future Applications: An Outlookmentioning
confidence: 99%